Efficacy of depression treatments for immigrant patients: Results from a systematic review - Antoniades, J.; Mazza, D.; Brijnath, Bianca (BioMed Central Ltd., 2014)
Background: The unprecedented rates of global migration present unique challenges to mental health services in migrant receiving countries to provide efficacious and culturally salient treatment for mental health conditions including depression. This review aimed to identify and evaluate the effectiveness of depression interventions specifically directed towards first-generation immigrant populations.Methods: We conducted a systematic review of original research published between 2000 and 2013 that investigated depression interventions in first generation immigrants.Results: Fifteen studies were included; the majority focused on Latino immigrants living in the United States (US). Twelve studies investigated the use of psychotherapies; the remainder examined collaborative care models and physical exercise-based interventions. Cognitive Behavioral Therapy and Behavioral Activation tended to improve depressive symptoms, especially when culturally adapted to suit clients while Problem Solving Therapy improved depressive symptomology with and without adaptations. Collaborative care and exercise did not significantly improve depressive symptoms.Conclusion: Depression may be effectively treated by means of psychotherapies, especially when treatments are culturally adapted. However the reviewed studies were limited due to methodological weaknesses and were predominantly undertaken in the US with Latino patients. To improve generalizability, future research should be undertaken in non-US settings, amongst diverse ethnic groups and utilize larger sample sizes in either randomized clinical trials or observational cohort studies. © 2014 Antoniades et al.; licensee BioMed Central Ltd.